TATA KELOLA INSTITUSI (INSTITUTIONAL ARRANGEMENT) KONTRAK MUDHARABA DALAM KERANGKA TEORI KEAGENAN - Manzilati, Asfi (Jurnal Ekonomi & Keuangan Islam, 2011)
This study offers an alternative governance (arrangement) mudharaba contract resulting mudharaba institutions that benefit both parties (principal and agent). With interviews obtained two important findings: first, the character of prospective clients is an important determinant of the creation of a contract as collateral material (should) not be used as a tool to compensate for the risk, and the second is that monitoring is key to the process of contract enforcement. Based on existing findings, to develop an institutional design that is expected mudharaba fair and beneficial to both parties, the bank / Shohibul mall as the principal and client / mudarib as an agent.